Liquid lead-acid battery
Patent Information
- Application Number
- JP2021120790
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-21
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-07-21
AI Technical Summary
【0010】 本発明の液式鉛蓄電池は、部分充電状態(例えば70%を超え100%未満の充電状態)で運用されるアイドリングストップ車に用いられた場合の充電受入性能に優れたものとなることが期待できる。
Smart Images

Figure 0007641839000005 
Figure 0007641839000006 
Figure 0007641839000001
Abstract
Description
[Technical field]
[0001] The present invention relates to flooded lead-acid batteries. [Background technology]
[0002] A typical flooded lead-acid battery includes a battery case having a cell chamber, a plate assembly housed in the cell chamber, an electrolyte injected into the cell chamber, and a lid fixed to the battery case to close the top of the cell chamber. The plate assembly includes a plurality of positive and negative plates arranged alternately, and a separator arranged between the positive and negative plates. The positive plate includes a positive current collector having a lattice substrate, and a positive electrode mixture (material containing a positive electrode active material) held by the lattice substrate. The negative plate includes a negative current collector having a lattice substrate, and a negative electrode mixture (material containing a negative electrode active material) held by the lattice substrate. The laminate is placed in the battery case with the plate surface of the lattice substrate aligned in the vertical direction of the battery case.
[0003] In recent years, due to exhaust gas regulations for automobiles, idling stop vehicles are rapidly becoming more common. In idling stop vehicles, the engine is stopped while the vehicle is stopped, and accessories such as the air conditioner and audio system are used with only the lead-acid battery as a power source. In addition, in order to improve fuel efficiency, lead-acid batteries in idle-stop vehicles are controlled so that they do not reach a fully charged state, and are operated in a partially charged state by intermittent charging. Therefore, if the charge acceptance of a lead-acid battery is insufficient, it is prone to becoming chronically undercharged.
[0004] When the charge state of a lead-acid battery becomes low, lead sulfate is formed on the positive and negative plates, and as the battery is repeatedly charged and discharged, the crystals of lead sulfate become coarse, and even if the battery is charged, the lead sulfate cannot return to its original active material (sulfation) occurs. In addition, since the battery is operated in a partially charged state, gassing of the electrolyte does not occur, which occurs when the battery is fully charged, and this makes it more likely that high-concentration sulfuric acid will accumulate at the bottom of the battery container (stratification). It is also known that stratification promotes sulfation.
[0005] Furthermore, the potential distribution of the plates of a lead-acid battery worsens from the top to the bottom of the battery case, so the lower parts of the plates (the positive and negative plates located at the bottom of the battery case) are particularly susceptible to sulfation. The potential distribution can be improved by making the current collector thicker, but unless the size of the cell chamber is changed, the number of plates that can be stored in the cell chamber will be reduced, making it difficult to improve battery performance.
[0006] Patent Documents 1 and 2 disclose a method for improving the charge acceptance of a flooded lead-acid battery by adding aluminum to the electrolyte and to at least one of the negative and positive electrode active materials. However, Patent Documents 1 and 2 do not disclose or suggest that the aluminum content of the negative and positive electrode active materials be made different in the vertical direction of a battery container having a grid-like substrate. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2005-317331 A [Patent Document 2] JP 2018-198151 A Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a flooded lead-acid battery that has excellent charge acceptance performance when used in an idle-stop vehicle operated in a partial state of charge (for example, a state of charge greater than 70% and less than 100%). [Means for solving the problem]
[0009] In order to solve the above problems, one aspect of the present invention provides a flooded lead-acid battery having the following configurations (a) to (c). (a) A battery case having a cell chamber, a plate group housed in the cell chamber, an electrolyte injected into the cell chamber, and a lid fixed to the battery case to close the top of the cell chamber. The plate group has a laminate made up of a plurality of alternately arranged positive and negative electrode plates and a separator arranged between the positive and negative electrode plates. (b) The positive electrode plate has a positive electrode current collector having a lattice substrate and a positive electrode mixture held by the lattice substrate. The negative electrode plate has a negative electrode current collector having a lattice substrate and a negative electrode mixture held by the lattice substrate. The laminate is placed in the battery case with the plate surface of the lattice substrate aligned along the vertical direction of the battery case. (c) At least one of the positive electrode mixture and the negative electrode mixture contains aluminum, and the aluminum content is higher in a lower part of the battery container of the grid-like substrate than in an upper part of the battery container. Effect of the Invention
[0010] The flooded lead-acid battery of the present invention is expected to have excellent charge acceptance performance when used in an idle-stop vehicle operated in a partial state of charge (for example, a state of charge greater than 70% but less than 100%). [Brief description of the drawings]
[0011] [Figure 1] 1 is a partial cross-sectional view showing a structure of a flooded lead-acid battery according to an embodiment. [Diagram 2] FIG. 2 is a plan view showing a positive electrode current collector plate constituting the flooded lead-acid battery of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to the embodiments shown below. In the embodiments shown below, technically preferable limitations are imposed for carrying out the present invention, but these limitations are not essential requirements for the present invention.
[0013] [Overall structure] 1, the flooded lead-acid battery of this embodiment includes a battery case 41 having a cell chamber, a plate group 1 housed in the cell chamber, an electrolyte (not shown) injected into the cell chamber, and a lid 43 fixed to the battery case 41 to close the top of the cell chamber. The plate group 1 includes a laminate including a plurality of alternately arranged positive electrode plates 10 and negative electrode plates 20, and a separator 30 disposed between the positive electrode plates 10 and the negative electrode plates 20.
[0014] One electrode plate group 1 is housed in one cell chamber, and the number of positive electrode plates 10 constituting the laminate of the electrode plate group 1 is equal to or less than the number of negative electrode plates 20. The number of positive electrode plates 10 may be the same as the number of negative electrode plates 20, or may be greater than the number of negative electrode plates 20. The positive electrode plate 10 has a positive electrode current collector and a positive electrode mixture containing a positive electrode active material, the positive electrode active material containing lead dioxide and aluminum. The positive electrode current collector has a rectangular lattice-shaped substrate and an ear 11 continuing to the lattice-shaped substrate, and the positive electrode mixture is held by the lattice-shaped substrate. The negative electrode plate 20 has a negative electrode current collector and a negative electrode mixture containing a negative electrode active material, the negative electrode active material containing metallic lead and aluminum. The negative electrode current collector has a rectangular lattice-shaped substrate and an ear 21 continuing to the lattice-shaped substrate, and the negative electrode mixture is held by the lattice-shaped substrate.
[0015] The positive electrode mixture and the negative electrode mixture are filled in the openings of the respective lattice substrates and cover the plate surfaces of the lattice substrates. The laminate of the electrode plate group 1 is disposed in the battery case 41 with the plate surfaces of the lattice-shaped substrates of the positive electrode plates 10 and the negative electrode plates 20 aligned in the up-down direction of the battery case 41 . The positive electrode current collector constituting the positive electrode plate 10 is formed by gravity casting using a Pb-Ca-Sn alloy. The negative electrode current collector constituting the negative electrode plate 20 is formed by continuous casting using a Pb-Ca-Sn alloy. Other manufacturing methods for the positive electrode current collector and the negative electrode current collector include a punching method for a rolled lead alloy plate and an expanding method using a rolled lead alloy plate. The separator 30 is, for example, a porous film-like body made of resin, glass, etc., and a pleated rib protruding in a direction perpendicular to the base surface may be formed on the flat base (film-like body).
[0016] The lugs 11 of the multiple positive electrode plates 10 are connected by a positive electrode strap 13, and the lugs 21 of the multiple negative electrode plates 20 are connected by a negative electrode strap 23. The positive electrode strap 13 is connected to one end of a positive electrode terminal 15, and the negative electrode strap 23 is connected to one end of a negative electrode terminal 25. The other end of the positive electrode terminal 15 and the other end of the negative electrode terminal 25 penetrate a lid 43 that closes the opening of a battery case 41, and are exposed to the outside of the case body of the flooded lead-acid battery consisting of the battery case 41 and the lid 43. The electrolyte contains aluminum ions in dilute sulfuric acid, and the aluminum ion concentration is 0.01 mol / L or more and 0.3 mol / L or less.
[0017] [Regarding the positive electrode mixture and the negative electrode mixture] 2, the positive electrode current collector 50 includes a horizontally long rectangular lattice-shaped substrate 510 and tabs 520 continuous with the lattice-shaped substrate 510. The lattice-shaped substrate 510 has an upper frame 511, a lower frame 512, a left frame 513, and a right frame 514 which form the four sides of the rectangle, a vertical center frame 516 connecting the upper frame 511 and the lower frame 512, and a horizontal center frame 517 connecting the left frame 513 and the right frame 514.
[0018] The lattice-shaped substrate 510 has an upper portion (a portion of the lattice-shaped substrate 510 disposed on the upper side of the battery case 41, an upper portion of the battery case 41) 531 on the upper frame 511 side of a horizontal center bone 517a located approximately midway between the upper frame 511 and the lower frame 512, and a lower portion (a portion of the lattice-shaped substrate 510 disposed on the lower side of the battery case 41, a lower portion of the battery case 41) 532 on the lower frame 512 side of the horizontal center bone 517a. The aluminum content in the lower portion 532 is higher than that in the upper portion 531, and the aluminum content in the lower portion 532 is 30 ppm or more and 90 ppm or less.
[0019] In addition, the specific surface area of the positive electrode mixture is 5m 2 / g or more 10m 2 / g or less. The negative electrode current collector plate has substantially the same shape as the positive electrode current collector plate 50, and the aluminum content of the negative electrode mixture held therein is higher in the lower portion 532 than in the upper portion 531, and the aluminum content in the lower portion 532 is 10 ppm or more and 60 ppm or less. The specific surface area of the negative electrode mixture is 0.5 m 2 / g or more 1.0m 2 / g or less. As a method for changing the aluminum content of the positive electrode mixture and the negative electrode mixture held in the lower portion 532 and the upper portion 531, there is a method in which the amount of an aluminum compound (e.g., aluminum sulfate or aluminum hydroxide) added to the positive electrode and negative electrode mixture paste to be attached to the lattice-shaped substrate 510 when producing the positive electrode plate 10 and the negative electrode plate 20 is changed between the lower portion 532 and the upper portion 531.
[0020] The "state in which the aluminum content of the aluminum-containing positive electrode mixture and negative electrode mixture is higher at the lower part than at the upper part in the battery container of the lattice substrate" can be obtained by changing the aluminum content between the upper and lower parts of the battery container of the lattice substrate, as in the positive electrode plate and negative electrode plate of this embodiment, with the vertical center of the battery container of the lattice substrate as the boundary, but the position at which the aluminum content changes may be below or above the vertical center of the battery container of the lattice substrate. It can also be obtained by continuously changing the aluminum content from the upper part to the lower part of the battery container of the lattice substrate.
[0021] [Action, effect] It is believed that aluminum improves the reactivity of lead sulfate by disintegrating the crystals when lead sulfate is produced in the battery reaction. In the flooded lead-acid battery of this embodiment, the aluminum content of the positive electrode mixture and the negative electrode mixture is higher in the lower part of the lattice substrate than in the upper part, so that the reactivity of lead sulfate in the lower part is increased, effectively suppressing sulfation that is likely to occur in the lower part of the lattice substrate due to stratification.
[0022] In addition, the aluminum contained in the positive electrode mixture becomes aluminum ions when it comes into contact with the electrolyte, and Pb 2+ Pb that is deficient during charging is absorbed by ions2+ This makes it possible to suppress polarization and increase charging efficiency by compensating for ions. In other words, when the charge state is between 70% and 100% and halfway through charging, the presence of a lot of aluminum, which facilitates oxidation reactions, at the bottom of the positive plate, which is prone to becoming undercharged, increases charging efficiency more effectively. In addition, the production of highly crystalline, irreversible lead sulfate is suppressed, preventing the positive electrode mixture from softening and falling off, which is expected to extend the battery's life.
[0023] Therefore, in the flooded lead-acid battery of this embodiment, even if the positive electrode mixture and the negative electrode mixture contain aluminum, compared to a flooded lead-acid battery in which the aluminum content is the same throughout the grid-like substrate or is higher in the upper part, sulfation, which is a cause of deterioration of the positive and negative electrode plates, is effectively suppressed, thereby improving charge acceptance characteristics and extending the idling stop life. In addition, the aluminum content in the lower part of the positive electrode mixture is 30 ppm or more and 90 ppm or less, and the aluminum content in the lower part of the negative electrode mixture is 10 ppm or more and 60 ppm or less. The specific surface area of the positive electrode mixture is 5 m 2 / g or more 10m 2 / g or less, and the specific surface area of the negative electrode mixture is 0.5 m 2 / g or more 1.0m 2 / g or less, the charge acceptance characteristics are further improved, and the idle stop life is further extended. EXAMPLES
[0024] [First Example] <Preparation of test battery> As flooded lead-acid batteries having the same structure as the flooded lead-acid battery of the embodiment, flooded lead-acid batteries of Samples No. 1-1 to No. 1-24 were fabricated in pairs. These flooded lead-acid batteries have a 20-hour rate capacity of 40 Ah, M-42 (JIS B20) size, and a nominal voltage of 12 V, and are all identical in structure except for the negative electrode mixture. The battery case has six cell compartments. First, current collector plates made of a Pb-Ca-Sn alloy were prepared as a positive current collector plate (grid substrate + tab) and a negative current collector plate (grid substrate + tab).
[0025] <Preparation of positive electrode plate (before chemical formation)> Lead powder containing lead monoxide as a main component was mixed with water and dilute sulfuric acid, and necessary additives were further added and kneaded to obtain a positive electrode mixture paste. The obtained positive electrode mixture paste was uniformly applied and filled onto the entire surface of the lattice substrate of the positive electrode current collector plate, and then aged and dried in a normal manner to produce a positive electrode plate (before chemical formation).
[0026] <Preparation of negative electrode plate (before chemical formation)> Six types of negative electrode mixture pastes were obtained by kneading lead powder, the main component of which was lead monoxide, with water, dilute sulfuric acid, and aluminum sulfate, and further mixing and kneading with necessary additives. Aluminum sulfate was mixed in a ratio of 0.062 to 0.863 parts by mass (corresponding to 5 to 70 ppm in the table when converted into aluminum sulfate 18-hydrate) per 100 parts by mass of lead powder.
[0027] The negative electrode plate (before chemical conversion) for Sample No. 1-1 was prepared by uniformly applying and filling a negative electrode mixture paste containing 0.062 parts by mass of aluminum sulfate onto the entire surface of the lattice substrate of the negative electrode current collector, and then aging and drying the paste in a conventional manner. The negative electrode plate (before chemical conversion) for Sample No. 1-2 was produced by uniformly applying and filling a negative electrode mixture paste having an aluminum sulfate content of 0.062 parts by mass onto an upper portion 531 (FIG. 2) of the lattice substrate of the negative electrode current collector, and a negative electrode mixture paste having an aluminum sulfate content of 0.123 parts by mass onto a lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector, and then aging and drying were performed in a conventional manner.
[0028] The negative electrode plate (before chemical conversion) for Sample No. 1-3 was prepared in the same manner as the negative electrode plate for Sample No. 1-2, except that a negative electrode mixture paste with an aluminum sulfate content of 0.247 parts by mass was used as the negative electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector. The negative electrode plate (before chemical conversion) for Sample No. 1-4 was prepared in the same manner as the negative electrode plate for Sample No. 1-2, except that a negative electrode mixture paste with an aluminum sulfate content of 0.493 parts by mass was used as the negative electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector.
[0029] The negative electrode plate (before chemical conversion) for Sample No. 1-5 was prepared in the same manner as the negative electrode plate for Sample No. 1-2, except that a negative electrode mixture paste with an aluminum sulfate content of 0.740 parts by mass was used as the negative electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector. The negative electrode plate (before chemical conversion) for Sample No. 1-6 was prepared in the same manner as the negative electrode plate for Sample No. 1-2, except that a negative electrode mixture paste with an aluminum sulfate content of 0.863 parts by mass was used as the negative electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector.
[0030] The negative electrode plate (before chemical conversion) for Sample No. 1-7 was prepared by uniformly applying and filling a negative electrode mixture paste containing 0.123 parts by mass of aluminum sulfate onto the entire surface of the lattice substrate of the negative electrode current collector, and then aging and drying the paste in the usual manner. The negative electrode plate (before chemical conversion) for Sample No. 1-8 was produced by uniformly applying and filling a negative electrode mixture paste having an aluminum sulfate content of 0.123 parts by mass onto an upper portion 531 (FIG. 2) of the lattice substrate of the negative electrode current collector, and a negative electrode mixture paste having an aluminum sulfate content of 0.247 parts by mass onto a lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector, and then aging and drying were performed in a normal manner.
[0031] The negative electrode plate (before chemical conversion) for Sample No. 1-9 was prepared in the same manner as the negative electrode plate for Sample No. 1-8, except that a negative electrode mixture paste with an aluminum sulfate content of 0.493 parts by mass was used as the negative electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector. The negative electrode plate (before chemical conversion) for Sample No. 1-10 was prepared in the same manner as the negative electrode plate for Sample No. 1-8, except that a negative electrode mixture paste with an aluminum sulfate content of 0.740 parts by mass was used as the negative electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector.
[0032] The negative electrode plate (before chemical conversion) for Sample No. 1-11 was prepared in the same manner as the negative electrode plate for Sample No. 1-8, except that a negative electrode mixture paste with an aluminum sulfate content of 0.863 parts by mass was used as the negative electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector. The negative electrode plate (before chemical conversion) for Sample No. 1-12 was produced by uniformly applying and filling a negative electrode mixture paste having an aluminum sulfate content of 0.247 parts by mass onto an upper portion 531 (FIG. 2) of the lattice substrate of the negative electrode current collector, and a negative electrode mixture paste having an aluminum sulfate content of 0.123 parts by mass onto a lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector, and then aging and drying were performed in a normal manner.
[0033] The negative electrode plate (before chemical conversion) for Sample No. 1-13 was prepared by uniformly applying and filling a negative electrode mixture paste containing 0.247 parts by mass of aluminum sulfate onto the entire surface of the lattice substrate of the negative electrode current collector, and then aging and drying the paste in a conventional manner. The negative electrode plate (before chemical conversion) for Sample No. 1-14 was prepared in the same manner as the negative electrode plate for Sample No. 1-12, except that a negative electrode mixture paste with an aluminum sulfate content of 0.493 parts by mass was used as the negative electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector.
[0034] The negative electrode plate (before chemical conversion) for Sample No. 1-15 was prepared in the same manner as the negative electrode plate for Sample No. 1-12, except that a negative electrode mixture paste with an aluminum sulfate content of 0.740 parts by mass was used as the negative electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector. The negative electrode plate (before chemical conversion) for Sample No. 1-16 was prepared in the same manner as the negative electrode plate for Sample No. 1-12, except that a negative electrode mixture paste with an aluminum sulfate content of 0.863 parts by mass was used as the negative electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector.
[0035] The negative electrode plate (before chemical conversion) for Sample No. 1-17 was produced by uniformly applying and filling a negative electrode mixture paste having an aluminum sulfate content of 0.493 parts by mass onto an upper portion 531 (FIG. 2) of the lattice substrate of the negative electrode current collector, and a negative electrode mixture paste having an aluminum sulfate content of 0.123 parts by mass onto a lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector, and then aging and drying were performed in a normal manner. The negative electrode plate (before chemical conversion) for Sample No. 1-18 was prepared in the same manner as the negative electrode plate for Sample No. 1-17, except that a negative electrode mixture paste with an aluminum sulfate content of 0.247 parts by mass was used as the negative electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector.
[0036] The negative electrode plate (before chemical conversion) for Sample No. 1-19 was prepared by uniformly applying and filling a negative electrode mixture paste containing 0.493 parts by mass of aluminum sulfate onto the entire surface of the lattice substrate of the negative electrode current collector, and then aging and drying the paste in a conventional manner. The negative electrode plate (before chemical conversion) for Sample No. 1-20 was prepared in the same manner as the negative electrode plate for Sample No. 1-17, except that a negative electrode mixture paste with an aluminum sulfate content of 0.740 parts by mass was used as the negative electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the negative electrode current collector. The negative electrode plates (before chemical formation) for Samples No. 1-21 to No. 1-24 were prepared to be the same as the negative electrode plate (before chemical formation) for Sample No. 1-14.
[0037] <Assembly> For each sample, the pre-chemical negative plate was placed in a polyethylene separator, and eight separators containing pre-chemical negative plates and seven pre-chemical positive plates were alternately stacked to obtain a laminate. Next, a cast-on-strap (COS) casting device was used to form straps, intermediate poles, and terminal poles on the pre-chemical positive and negative plates of each laminate to obtain a plate group.
[0038] Six of these electrode plate groups were prepared for each sample, and placed in each cell chamber of the battery case. Flooded lead-acid batteries (before chemical formation) for No. 1-1 to No. 1-24 were assembled by carrying out the usual processes, such as resistance welding of the intermediate poles between adjacent cell chambers, heat welding of the battery case and the lid, injection of electrolyte into each cell chamber through each injection hole, and sealing the injection holes. The electrolyte was injected into each cell chamber by injecting a liquid prepared by adding aluminum sulfate to dilute sulfuric acid with a specific gravity of 1.220 (calculated at 20°C) to give a concentration of 31.3 g / L.
[0039] Then, the container was formed to have a specific gravity of 1.285 (20°C equivalent) for the electrolyte after container formation, thereby obtaining flooded lead-acid batteries No. 1-1 to No. 1-24. Note that the higher the formation temperature, the smaller the specific surface area of the negative electrode mixture. Therefore, the formation temperature during container formation was appropriately changed until the specific surface area of the negative electrode mixture was 0.7 m for No. 1-1 to No. 1-20. 2 / g, No.1-21 is 0.4m 2 / g, 0.5m for No.1-22 2 / g, No.1-23 is 1.0m 2 / g, 1.2m for No.1-24 2 / g.
[0040] <Measurement of aluminum content in negative electrode mixture> Each of the obtained No.1-1 to No.1-24 flooded lead-acid batteries (fully charged state) was disassembled, the negative electrode plate in a predetermined position was removed, and the negative electrode mixture held in the opening adjacent to the upper frame of the lattice substrate and the negative electrode mixture held in the opening adjacent to the lower frame were scraped off and crushed separately to obtain powdered upper and lower part samples for each sample. Each of the obtained samples was subjected to an ICP emission spectrometer to measure the aluminum content of the negative electrode mixture held in each part.
[0041] <Measurement of the specific surface area of the negative electrode mixture> For each sample, the remaining negative electrode mixture was scraped off from the negative electrode plate from which the aluminum content measurement negative electrode mixture had been scraped off, and the negative electrode mixture was pulverized to obtain a sample for specific surface area measurement. The specific surface area of the negative electrode mixture was measured by the BET method using each of the obtained samples.
[0042] <Testing and Evaluation> Using each of the resulting flooded lead-acid batteries, tests were carried out in the following manner. [Performance test] The resulting No. 1-1 to No. 1-24 flooded lead-acid batteries were subjected to an idling stop life test in the following manner. This test was conducted in accordance with the "Japan Battery Industry Association Standard SBA S0101:2014 Idling Stop Life Test" and the test procedure was as follows. First, the flooded lead-acid battery was charged in the gas phase at 25°C with a charging current of 0.1 ItA until the SOC (state of charge) reached 100%, and then the 20-hour rate capacity C 20,n and 20-hour rate current I 20 Next, I was measured in the gas phase at 25°C. 20 A series of charge-discharge cycles were repeated, consisting of a constant current discharge at a current value 18.3 times the normal current for 59 seconds, followed by a constant current discharge at a current value of 300 A for 1 second, and then a constant current-constant voltage charge at a constant current of 100 A and a constant voltage of 14.0 V for 60 seconds.
[0043] The battery was deemed to have reached the end of its life when the discharge voltage during the test fell below 7.2 V, and the number of charge / discharge cycles up to that point was measured as the SBA life. During the test, the battery was left to sit for 40 hours every 3600 cycles. In addition, since this test tends to suppress the charge capacity relative to the discharge capacity low, this test is suitable for judging the quality of the charging efficiency.
[0044] In addition, if the SBA life is 32,000 cycles or more, it is determined that the battery has a sufficiently long idling stop life, and therefore the lead-acid battery has excellent life characteristics in a low SOC state. Therefore, for each SBA life measured for the flooded lead-acid batteries No. 1-1 to No. 1-24, a relative value was calculated with the SBA life of 32,000 cycles set as "100". Furthermore, if the SBA life is 34,000 cycles or more (relative value 107), it is determined that the battery has a particularly long idling stop life, and therefore the lead-acid battery has excellent life characteristics in a low SOC state.
[0045] The test results for No. 1-1 to No. 1-20 are shown in Table 1 together with the aluminum content of the negative electrode mixture of each flooded lead-acid battery. The specific surface area of the negative electrode mixtures of No. 1-1 to No. 1-20 is all 0.7 m 2 / g. For No.1-14 and No.1-21 to No.1-24, the test results and the measurement results of the specific surface area of the negative electrode mixture are shown in Table 2 together with the aluminum content of the negative electrode mixture of each flooded lead-acid battery. In addition, Tables 1 and 2 have a judgment item, and a relative value of SBA life of less than 100 is shown as "x", a value of 100 to 106 is shown as "o", and a relative value of 107 or more is shown as "◎".
[0046] [Table 1]
[0047] [Table 2]
[0048] The results in Table 1 reveal the following: The lead-acid batteries No. 1-1 to No. 1-6 have the same aluminum content of the negative electrode mixture in the upper part, which is 5 ppm, but the lead-acid batteries No. 1-2 to No. 1-6, in which the aluminum content of the negative electrode mixture is higher in the lower part than in the upper part, have an SBA life that is more than 1.03 (= 100 / 97) times longer than that of the lead-acid battery No. 1-1, in which the aluminum content of the negative electrode mixture is the same in the lower and upper parts, and have excellent life characteristics at low SOC.
[0049] In addition, among the lead-acid batteries No. 1-2 to No. 1-6, the lead-acid batteries No. 1-2 to No. 1-5, which have an aluminum content of 10 ppm or more and 60 ppm or less in the lower part, have a longer SBA life than the lead-acid battery No. 1-6, which has an aluminum content of 70 ppm, and are 1.12 (= 109 / 97) times or more and 1.21 (= 117 / 97) times or less than that of the lead-acid battery No. 1-1, and are particularly excellent in terms of life characteristics under low SOC conditions. The lead-acid batteries No. 1-7 to No. 1-11 have the same aluminum content of the negative electrode mixture in the upper part, which is 10 ppm, but the lead-acid batteries No. 1-8 to No. 1-11, in which the aluminum content of the negative electrode mixture is higher in the lower part than in the upper part, have an SBA life that is more than 1.03 (= 100 / 97) times longer than that of the lead-acid battery No. 1-7, in which the aluminum content of the negative electrode mixture is the same in the lower and upper parts, and have excellent life characteristics at a low SOC.
[0050] In addition, among the lead-acid batteries No. 1-8 to No. 1-11, the lead-acid batteries No. 1-8 to No. 1-10, which have an aluminum content of 20 ppm or more and 60 ppm or less in the lower part, have a longer SBA life than the lead-acid battery No. 1-11, which has an aluminum content of 70 ppm, and are 1.11 (= 108 / 97) times or more and 1.23 (= 119 / 97) times or less than that of the lead-acid battery No. 1-7, and are particularly excellent in terms of life characteristics under low SOC conditions. The lead-acid batteries No. 1-12 to No. 1-16 have the same aluminum content of the negative electrode mixture in the upper part, which is 20 ppm, but the lead-acid batteries No. 1-14 to No. 1-16, in which the aluminum content of the negative electrode mixture is higher in the lower part than in the upper part, have an SBA life that is more than 1.03 (= 101 / 98) times longer than that of the lead-acid battery No. 1-13, in which the aluminum content of the negative electrode mixture is the same in the lower and upper parts, and have excellent life characteristics at a low SOC.
[0051] In addition, among the lead-acid batteries No. 1-12 to No. 1-16, the lead-acid batteries No. 1-14 to No. 1-15, which have an aluminum content of 40 ppm or more and 60 ppm or less in the lower part, have a longer SBA life than the lead-acid battery No. 1-16, which has an aluminum content of 70 ppm, and are 1.13 (= 111 / 98) times or more and 1.28 (= 125 / 98) times or less than that of the lead-acid battery No. 1-13, and are particularly excellent in terms of life characteristics under low SOC conditions. The lead-acid batteries No. 1-17 to No. 1-20 have the same aluminum content of the negative electrode mixture in the upper part, which is 40 ppm. However, the lead-acid battery No. 1-20, in which the aluminum content of the negative electrode mixture is higher in the lower part than in the upper part, has an SBA life that is 1.10 (= 108 / 98) times longer than the lead-acid battery No. 1-19, in which the aluminum content of the negative electrode mixture is the same in the lower and upper parts, and has excellent life characteristics at low SOC.
[0052] The results in Table 2 reveal the following: The lead-acid batteries No. 1-14 and No. 1-21 to No. 1-24 have the same aluminum content in the upper part of the negative electrode mixture, 20 ppm, and the same value in the lower part, 40 ppm, but the specific surface area of the negative electrode mixture is 0.5 m 2 / g or more 1.0m 2 The lead-acid batteries No. 1-14, No. 1-22, and No. 1-23, which are less than 0.4m 2 / g, 1.2m 2 / g, and is 1.08 to 1.25 times that of the lead-acid battery No. 1-6, and is particularly excellent in life characteristics under low SOC conditions.
[0053] From the above, it was confirmed that the aluminum content of the negative electrode mixture is higher in the lower part of the lattice substrate than in the upper part, improving the charge acceptance characteristics and lengthening the idling stop life. In addition, when the aluminum content of the negative electrode mixture is higher in the lower part of the lattice substrate than in the upper part, and the aluminum content in the lower part is 10 ppm or more and 60 ppm or less, and the specific surface area of the negative electrode mixture is 0.5 m 2 / g or more 1.0m 2 It was confirmed that when the carbon black has a capacitance of 1.0 μm or less, the charge acceptance characteristic is significantly improved and the idle stop life is significantly extended.
[0054] [Second embodiment] <Preparation of test battery> As flooded lead-acid batteries having the same structure as the flooded lead-acid battery of the embodiment, flooded lead-acid batteries of Samples No. 2-1 to No. 2-24 were fabricated in pairs. These flooded lead-acid batteries have a 20-hour rate capacity of 40 Ah, M-42 (JIS B20) size, and a nominal voltage of 12 V, and are all identical in structure except for the positive electrode mixture. The battery case has six cell compartments. First, current collector plates made of a Pb-Ca-Sn alloy were prepared as a positive current collector plate (grid substrate + tab) and a negative current collector plate (grid substrate + tab).
[0055] <Preparation of negative electrode plate (before chemical formation)> Lead powder containing lead monoxide as a main component was mixed with water and dilute sulfuric acid, and necessary additives were further added and kneaded to obtain a negative electrode mixture paste. The obtained negative electrode mixture paste was uniformly applied and filled onto the entire surface of the lattice substrate of the negative electrode current collector plate, and then aged and dried in a normal manner to produce a negative electrode plate (before chemical formation).
[0056] <Preparation of positive electrode plate (before chemical formation)> Seven types of positive electrode mixture pastes were obtained by kneading lead powder, the main component of which was lead monoxide, with water, dilute sulfuric acid, and aluminum sulfate, and further mixing and kneading with necessary additives. Aluminum sulfate was mixed in a ratio of 0.247 to 1.233 parts by mass (corresponding to 20 to 100 ppm in the table in terms of aluminum sulfate 18-hydrate) per 100 parts by mass of lead powder.
[0057] The positive electrode plate (before chemical conversion) for Sample No. 2-1 was prepared by uniformly applying and filling a positive electrode mixture paste containing 0.247 parts by mass of aluminum sulfate onto the entire surface of the lattice substrate of the positive electrode current collector, and then aging and drying the paste in a conventional manner. The positive electrode plate (before chemical conversion) for Sample No. 2-2 was produced by uniformly applying and filling a positive electrode mixture paste having an aluminum sulfate content of 0.247 parts by mass onto upper portion 531 (FIG. 2) of the lattice substrate of the positive electrode current collector, and a positive electrode mixture paste having an aluminum sulfate content of 0.370 parts by mass onto lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector, and then aging and drying were performed in a normal manner.
[0058] The positive electrode plate (before chemical conversion) for Sample No. 2-3 was prepared in the same manner as the positive electrode plate for Sample No. 2-2, except that a positive electrode mixture paste with an aluminum sulfate content of 0.617 parts by mass was used as the positive electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector. The positive electrode plate (before chemical conversion) for Sample No. 2-4 was produced in the same manner as the positive electrode plate for Sample No. 2-2, except that a positive electrode mixture paste with an aluminum sulfate content of 1.110 parts by mass was used as the positive electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector.
[0059] The positive electrode plate (before chemical conversion) for Sample No. 2-5 was prepared in the same manner as the positive electrode plate for Sample No. 2-2, except that a positive electrode mixture paste containing 1.223 parts by mass of aluminum sulfate was used as the positive electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector. The positive electrode plate (before chemical conversion) for Sample No. 2-6 was prepared by uniformly applying and filling a positive electrode mixture paste containing 0.370 parts by mass of aluminum sulfate onto the entire surface of the lattice substrate of the positive electrode current collector, and then aging and drying the paste in a conventional manner.
[0060] The positive electrode plate (before chemical conversion) for Sample No. 2-7 was produced by uniformly applying and filling a positive electrode mixture paste having an aluminum sulfate content of 0.370 parts by mass onto upper portion 531 (FIG. 2) of the lattice substrate of the positive electrode current collector, and a positive electrode mixture paste having an aluminum sulfate content of 0.555 parts by mass onto lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector, and then aging and drying were performed in a normal manner. The positive electrode plate (before chemical conversion) for Sample No. 2-8 was prepared in the same manner as the positive electrode plate for Sample No. 2-7, except that a positive electrode mixture paste containing 1.110 parts by mass of aluminum sulfate was used as the positive electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector.
[0061] The positive electrode plate (before chemical conversion) for Sample No. 2-9 was prepared in the same manner as the positive electrode plate for Sample No. 2-7, except that a positive electrode mixture paste containing 1.223 parts by mass of aluminum sulfate was used as the positive electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector. The positive electrode plate (before chemical conversion) for Sample No. 2-10 was produced by uniformly applying and filling a positive electrode mixture paste having an aluminum sulfate content of 0.617 parts by mass onto an upper portion 531 (FIG. 2) of the lattice substrate of the positive electrode current collector, and a positive electrode mixture paste having an aluminum sulfate content of 0.247 parts by mass onto a lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector, and then aging and drying were performed in a normal manner.
[0062] The positive electrode plate (before chemical conversion) for Sample No. 2-11 was prepared in the same manner as the positive electrode plate for Sample No. 2-10, except that a positive electrode mixture paste with an aluminum sulfate content of 0.370 parts by mass was used as the positive electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector. The positive electrode plate (before chemical conversion) for Sample No. 2-12 was prepared by uniformly applying and filling a positive electrode mixture paste containing 0.617 parts by mass of aluminum sulfate onto the entire surface of the lattice substrate of the positive electrode current collector, and then aging and drying the paste in a conventional manner.
[0063] The positive electrode plate (before chemical conversion) for Sample No. 2-13 was produced in the same manner as the positive electrode plate for Sample No. 2-10, except that a positive electrode mixture paste containing 0.925 parts by mass of aluminum sulfate was used as the positive electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector. The positive electrode plate (before chemical conversion) for Sample No. 2-14 was prepared in the same manner as the positive electrode plate for Sample No. 2-10, except that a positive electrode mixture paste containing 1.110 parts by mass of aluminum sulfate was used as the positive electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector.
[0064] The positive electrode plate (before chemical conversion) for Sample No. 2-15 was prepared in the same manner as the positive electrode plate for Sample No. 2-10, except that a positive electrode mixture paste containing 1.223 parts by mass of aluminum sulfate was used as the positive electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector. The positive electrode plate (before chemical conversion) for Sample No. 2-16 was produced by uniformly applying and filling a positive electrode mixture paste having an aluminum sulfate content of 1.110 parts by mass onto an upper portion 531 (FIG. 2) of the lattice substrate of the positive electrode current collector, and a positive electrode mixture paste having an aluminum sulfate content of 0.247 parts by mass onto a lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector, and then aging and drying were performed in a normal manner.
[0065] The positive electrode plate (before chemical conversion) for Sample No. 2-17 was prepared in the same manner as the positive electrode plate for Sample No. 2-16, except that a positive electrode mixture paste with an aluminum sulfate content of 0.370 parts by mass was used as the positive electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector. The positive electrode plate (before chemical conversion) for Sample No. 2-18 was prepared in the same manner as the positive electrode plate for Sample No. 2-16, except that a positive electrode mixture paste with an aluminum sulfate content of 0.617 parts by mass was used as the positive electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector.
[0066] The positive electrode plate (before chemical conversion) for Sample No. 2-19 was prepared by uniformly applying and filling a positive electrode mixture paste containing 1.110 parts by mass of aluminum sulfate onto the entire surface of the lattice substrate of the positive electrode current collector, and then aging and drying the paste in a conventional manner. The positive electrode plate (before chemical conversion) for Sample No. 2-20 was prepared in the same manner as the positive electrode plate for Sample No. 2-16, except that a positive electrode mixture paste containing 1.223 parts by mass of aluminum sulfate was used as the positive electrode mixture paste to be applied and filled into the lower portion 532 (FIG. 2) of the lattice substrate of the positive electrode current collector. The positive electrode plates (before chemical formation) for Samples No. 2-21 to No. 2-24 were prepared to be the same as the positive electrode plate (before chemical formation) for Sample No. 2-7.
[0067] <Assembly> Flooded lead-acid batteries (before chemical formation) for No. 2-1 to No. 2-24 were assembled in the same manner as in the first embodiment, except that a different positive electrode plate (before chemical formation) was used for each sample. The electrolyte was injected into each cell chamber by injecting a liquid prepared by adding aluminum sulfate to dilute sulfuric acid with a specific gravity of 1.220 (calculated at 20°C) to give a concentration of 31.3 g / L. Then, the container was formed to have a specific gravity of 1.285 (20°C equivalent) for the electrolyte after container formation, thereby obtaining flooded lead-acid batteries No. 2-1 to No. 2-24. Note that the higher the formation temperature, the smaller the specific surface area of the positive electrode mixture. Therefore, the formation temperature during container formation was appropriately changed to obtain a specific surface area of the positive electrode mixture of 8 m for No. 2-1 to No. 2-20. 2 / g, 4m for No.2-21 2 / g, 5m for No.2-22 2 / g, 10m for No.2-23 2 / g, 12m for No.2-24 2 / g.
[0068] <Measurement of aluminum content in positive electrode mixture> Each of the obtained No. 2-1 to No. 2-24 flooded lead-acid batteries (fully charged state) was disassembled, the positive electrode plate in a predetermined position was removed, and the positive electrode mixture held in the opening adjacent to the upper frame of the lattice substrate and the positive electrode mixture held in the opening adjacent to the lower frame were scraped off and crushed separately to obtain powdered samples for the upper and lower parts for each sample. Each of the obtained samples was subjected to an ICP emission spectrometer to measure the aluminum content of the positive electrode mixture held in each part.
[0069] <Measurement of the specific surface area of the positive electrode mixture> For each sample, the remaining positive electrode mixture was scraped off from the positive electrode plate from which the positive electrode mixture for measuring the aluminum content had been scraped off, and the plate was pulverized to obtain a sample for measuring the specific surface area. The specific surface area of the positive electrode mixture was measured by the BET method using each of the obtained samples.
[0070] <Testing and Evaluation> Using each of the resulting flooded lead-acid batteries No. 2-1 to No. 2-24, a test was carried out in the same manner as in the first example. If the SBA life is 32,000 cycles or more, it is determined that the battery has a sufficiently long idling stop life, and therefore is a lead-acid battery with excellent life characteristics in a low SOC state. Therefore, for each SBA life measured for the flooded lead-acid batteries No. 2-1 to No. 2-24, a relative value was calculated with the SBA life of 32,000 cycles set as "100". In addition, if the SBA life is 34,000 cycles or more (relative value 107), it is determined that the battery has a particularly long idling stop life, and therefore is a lead-acid battery with particularly excellent life characteristics in a low SOC state.
[0071] The test results for No. 2-1 to No. 2-20 are shown in Table 3 together with the aluminum content of the positive electrode mixture of each flooded lead-acid battery. The specific surface area of the positive electrode mixture of No. 2-1 to No. 2-20 is all 8 m 2 / g. For No. 2-14 and No. 2-21 to No. 2-24, the test results and the measurement results of the specific surface area of the positive electrode mixture are shown in Table 4 together with the aluminum content of the positive electrode mixture of each flooded lead-acid battery. In addition, Tables 3 and 4 have a judgment item, and a relative value of SBA life of less than 100 is shown as "x", a relative value of 100 to 106 is shown as "o", and a relative value of 107 or more is shown as "◎".
[0072] [Table 3]
[0073] [Table 4]
[0074] The results in Table 3 reveal the following: The lead-acid batteries No. 2-1 to No. 2-5 have the same aluminum content of the positive electrode mixture in the upper part, which is 20 ppm, but the lead-acid batteries No. 2-2 to No. 2-5, in which the aluminum content of the positive electrode mixture is higher in the lower part than in the upper part, have an SBA life that is more than 1.03 (= 100 / 97) times longer than that of the lead-acid battery No. 2-1, in which the aluminum content of the positive electrode mixture is the same in the upper and lower parts, and have excellent life characteristics at low SOC.
[0075] In addition, among the lead-acid batteries No. 2-2 to No. 2-5, the lead-acid batteries No. 2-2 to No. 2-4, which have an aluminum content of 30 ppm or more and 90 ppm or less in the lower part, have a longer SBA life than the lead-acid battery No. 2-5, which has an aluminum content of 100 ppm, and are 1.10 (= 107 / 97) times or more and 1.21 (= 117 / 97) times or less than that of the lead-acid battery No. 2-1, and are particularly excellent in terms of life characteristics under low SOC conditions. The lead-acid batteries No. 2-6 to No. 2-9 have the same aluminum content of the positive electrode mixture in the upper part, which is 30 ppm, but the lead-acid batteries No. 2-7 to No. 2-9, in which the aluminum content of the positive electrode mixture is higher in the lower part than in the upper part, have an SBA life that is more than 1.10 (= 106 / 96) times longer than that of the lead-acid battery No. 2-6, in which the aluminum content of the positive electrode mixture is the same in the upper and lower parts, and have excellent life characteristics at low SOC.
[0076] In addition, among the lead-acid batteries No. 2-7 to No. 2-9, the lead-acid batteries No. 2-7 to No. 2-8, which have an aluminum content of 45 ppm or more and 90 ppm or less in the lower part, have a longer SBA life than the lead-acid battery No. 2-9, which has an aluminum content of 100 ppm, and are 1.13 (= 109 / 96) times or more and 1.31 (= 126 / 96) times or less than that of the lead-acid battery No. 2-6, and are particularly excellent in terms of life characteristics under low SOC conditions. The lead-acid batteries No. 2-10 to No. 2-15 have the same aluminum content of the positive electrode mixture at the upper part, which is 50 ppm, but the lead-acid batteries No. 2-13 to No. 2-15, in which the aluminum content of the positive electrode mixture is higher in the lower part than in the upper part, have an SBA life that is 1.08 (= 106 / 98) times or more and 1.19 (= 117 / 98) times or less than that of the lead-acid battery No. 2-12, in which the aluminum content of the positive electrode mixture is the same in the lower and upper parts, and have excellent life characteristics at a low SOC.
[0077] In addition, among the lead-acid batteries No. 2-13 to No. 2-15, the lead-acid batteries No. 2-13 to No. 2-14, which have an aluminum content of 75 ppm or more and 90 ppm or less in the lower part, have a longer SBA life than the lead-acid battery No. 2-15, which has an aluminum content of 100 ppm, and are 1.09 (= 107 / 98) times or more and 1.19 (= 117 / 98) times or less than that of the lead-acid battery No. 2-12, and are particularly excellent in terms of life characteristics under low SOC conditions. The lead-acid batteries No. 2-16 to No. 2-20 have the same aluminum content of the positive electrode mixture in the upper part, which is 90 ppm. However, the lead-acid battery No. 2-20, in which the aluminum content of the positive electrode mixture is higher in the lower part than in the upper part, has an SBA life that is 1.08 (= 105 / 97) times longer than the lead-acid battery No. 2-19, in which the aluminum content of the positive electrode mixture is the same in the upper and lower parts, and has excellent life characteristics when the SOC is low.
[0078] The results in Table 4 reveal the following: The lead-acid batteries No. 2-7 and No. 2-21 to No. 2-24 have the same aluminum content in the upper part of the positive electrode mixture, 30 ppm, and the same value in the lower part, 45 ppm, but the specific surface area of the positive electrode mixture is 5 m 2 / g or more 10m 2 The lead-acid batteries No. 2-7, No. 2-22, and No. 2-23, which have a density of 4m 2 / g, 12m 2 / g, and is 1.17 to 1.26 times that of the lead-acid battery No. 2-5, showing particularly excellent life characteristics under low SOC conditions.
[0079] From the above, it was confirmed that the aluminum content of the positive electrode mixture is higher in the lower part of the lattice substrate than in the upper part, improving the charge acceptance characteristics and lengthening the idling stop life. In addition, when the aluminum content of the positive electrode mixture is higher in the lower part of the lattice substrate than in the upper part, and the aluminum content in the lower part is 30 ppm or more and 90 ppm or less, and the specific surface area of the positive electrode mixture is 5 m 2 / g or more 10m 2 It was confirmed that when the carbon black has a capacitance of 1.0 μm or less, the charge acceptance characteristic is significantly improved and the idle stop life is significantly extended. [Explanation of symbols]
[0080] 1 Plate group 10 Positive electrode plate 20 Negative plate 30 Separator 41 Battery case 43 Lid 50 Positive current collector 510 Lattice substrate 511 Upper frame 512 Lower frame bone 513 Left frame bone 514 Right frame bone 516 Longitudinal bone 517 Side bone 517a A transverse bone located approximately halfway between the upper and lower bones 520 Ear 531 Upper part of the grid-like substrate (upper part of the battery case) 532 Lower part of the grid-like substrate (lower part of the battery container)
Claims
1. a battery case having a cell chamber; A plate group housed in the cell chamber; an electrolyte injected into the cell chamber; a cover fixed to the battery case and closing an upper portion of the cell chamber; Equipped with the electrode plate group has a laminate including a plurality of alternately arranged positive electrode plates and negative electrode plates and a separator disposed between the positive electrode plates and the negative electrode plates; The positive electrode plate includes a positive electrode current collector having a lattice substrate and a positive electrode mixture held by the lattice substrate, The negative electrode plate includes a negative electrode current collector plate having a lattice substrate and a negative electrode mixture held by the lattice substrate, The laminate is placed in the battery container with the plate surface of the lattice-shaped substrate aligned in the up-down direction of the battery container, At least one of the positive electrode mixture and the negative electrode mixture contains aluminum, and the aluminum content is higher in a lower part of the battery case of the grid-shaped substrate than in an upper part of the battery case.
2. 2. The flooded lead-acid battery in accordance with claim 1, wherein the positive electrode mixture contains aluminum, and the aluminum content in the lower portion of the grid substrate in the battery case is 30 ppm or more and 90 ppm or less.
3. The specific surface area of the positive electrode mixture is 5 m 2 / g or more 10m 2 3. The flooded lead-acid battery according to claim 2, wherein the capacitance is 0.1 to 1.0 μm.
4. 2. The flooded lead-acid battery in accordance with claim 1, wherein the negative electrode mixture contains aluminum, and the aluminum content in the lower portion of the grid substrate in the battery case is 10 ppm or more and 60 ppm or less.
5. The specific surface area of the negative electrode mixture is 0.5 m 2 / g or more 1.0m 2 5. The flooded lead-acid battery according to claim 4, wherein the capacitance is 0.1 to 0.5 μm.
Citation Information
Patent Citations
Lead-acid battery
JP2005317331A
Lead storage battery
JP2018198151A